Gibran and His AI Narrative: A Digital Discourse Analysis of Innovation, Modernity, and Power - Amrurobbi, Azka Abdi; Mahadika, Alam (Faculty of Social and Political Science Universitas Brawijaya, 2026)
This study examines the construction, dissemination, and framing of Artificial Intelligence (AI) narratives associated with Indonesian Vice President Gibran Rakabuming Raka in online mass media during his first year in office (October 2024–October 2025). Drawing on political symbolism and political branding frameworks, AI is reconceptualized not merely as a technical instrument but as a strategic symbolic resource deployed to build political legitimacy and project a future-oriented leadership image. The novelty of this study lies in its hybrid methodological approach that integrates critical discourse analysis (CDA) with computational topic modeling (Latent Dirichlet Allocation/LDA), while performing a unique technological triangulation by comparing the performance of three Python libraries—Gensim, Scikit-learn, and Tomotopy—to map digital political discourse in Indonesia, an area hitherto underexplored. Analyzing 540 online news articles, the research identifies five core discursive themes, including AI integration in Islamic boarding schools (pesantren), collaborations with global tech giants, school curriculum adoption, and deepfake-driven political hoaxes. Computational evaluation demonstrates that Tomotopy yields the best semantic consistency, achieving the highest coherence score (0.653). Ultimately, beneath the pervasive technological optimism, this study concludes that the AI narrative serves as an instrument of symbolic power that actively obscures structural digital infrastructure disparities between regions, offering vital theoretical and methodological contributions to digital politics in developing nations.